SLBQT-DSR: SOURCE-BASED LOAD BALANCING ROUTING ALGORITHM UNDER CONSTRAINTS OF QUALITY OF TRANSMISION FOR MANET - Binh, Le Huu; Tu, Vo Thanh; Tam, Nguyen Van (Journal of Computer Science and Cybernetics, 2018)
The routing technique under the constraints of the quality of transmision (QoT) in mobile ad hoc networks (MANET) has been studied widely recently. For this routing technique, QoT of the data transmission routes is improved. However, for the network models with mesh topologies such as MANET, The routing technique under the constraints of QoT can increase the bottlenecks due to the unbalanced traffic load. In this paper, we improve the DSR protocol by using the source-based load balancing in combined with the QoT constraint. The simulation results have shown that, the proposed algorithm outperforms the original algorithms in terms of the signal to noise ratio, bit error rate, blocking probability of the data packets and throughput.The routing technique under the constraints of the quality of transmision (QoT) inmobile ad hoc networks (MANET) has been studied widely recently. For this routing technique, QoTof the data transmission routes is improved. However, for the network models with mesh topologiessuch as MANET, The routing technique under the constraints of QoT can increase the bottlenecksdue to the unbalanced trac load. In this paper, we improve the DSR protocol by using the source-based load balancing in combined with the QoT constraint. The simulation results have shown that,the proposed algorithm outperforms the original algorithms in terms of the signal to noise ratio, biterror rate, blocking probability of the data packets and throughput